ОЦЕНКА ОРГАНИЗАЦИИ САМОСТОЯТЕЛЬНОЙ РАБОТЫ СТУДЕНТОВ НА КАФЕДРЕ МЕДИЦИНСКОЙ ИНФОРМАТИКИ - Тихомирова, Александра Александровна; Ваулин, Георгий Федорович; Котиков, Павел Евгеньевич; Дохов, Михаил Александрович (Медицина: теория и практика, 2020)